PsicoCare: a pilot randomized controlled trial testing a psychological intervention combining cognitive-behavioral treatment and positive psychology therapy in acute coronary syndrome patients - Magán, Inés; Jurado-Barba, Rosa; Moreno, Guillermo; Ayán-Sanz, María Paz; Izquierdo-Garcia, Juan; Corradi, Guido; Tello, Rocio; Bueno, Héctor (Frontiers in Psychology, 2024)
Background: Although psychological factors contribute to acute coronary syndrome (ACS) onset and prognosis, psychological interventions (PIs) are rarely included in cardiac rehabilitation (CR) programs due to inconclusive evidence on specific intervention components and effect sizes. The aim of this study was to assess the efficacy of a PI based on cognitive-behavioral treatment (CBT) and positive psychology therapy (PPT) in improving psychological and clinical outcomes in patients with ACS.Methods: The PsicoCare trial, an open-label randomized controlled trial, compared a combined CBT and PPT-based PI (PsicoCare program) with a standard CR program (control group). The study recruited 87 ACS patients, and psychological outcomes, functional capacity, biochemical and anthropometric measures, and clinical outcomes were assessed at baseline, two months, and nine months after the ACS event.Results: The PsicoCare group showed significant improvements in depression, anger trait, anger-in, and anger control-out compared to the control group. Additionally, the PsicoCare intervention maintained more functional cognitive, social support, and spiritual coping styles, while the control group deteriorated. Patients experiencing severe ACS showed significant improvement in the personal strength of meaning due to the PsicoCare intervention. However, no significant effects were observed on anxiety, anger-out, emotion regulation skills, dispositional optimism, other personal strengths, or quality of life. Both groups achieved similar improvements in functional capacity and clinical outcomes.The study suggests that CBT and PPT-based PIs may offer additional benefits for ACS patients, particularly at a psychological level, and further larger trials are needed to confirm these findings.